Student Management in Competency Improvement and Character Development of Learners - Izzaty, Arina; Jinan, Mutohharun (Universitas Negeri Malang, 2024)
Abstract: The implementation of learning activities in schools can run because of the presence of students who are the main part in the process of transmitting knowledge. Therefore, the existence of students needs to be managed properly. Thus, a good student management system must be established to support the growth and development of students according to their potential and intelligence. This study aims to explain student management to improve the competence and character development of students at MA PPMI Assalaam Sukoharjo. This research uses a qualitative approach with the type of field study. Data were obtained from observations, interviews and documentation. While data analysis uses data reduction techniques, data presentation and conclusion drawing referring to the Miles & Huberman technique. The results showed that the student management process implemented was proven to be able to improve students. Through student management, MA PPMI tries to give progress to children every morning, namely when in the morning they come on time, they are given a reward by giving good words. In addition, MA PPMI Assalaam Sukoharjo also has a special program, namely by holding an evening study program. Student management has a significant role in improving the competence and character development of students as well as in the aspect of character building. Through character building programs organized by the boarding school, learners are given the opportunity to develop Islamic values, leadership, togetherness, and responsibility, all of which are important factors in achieving academic and life success.Keywords: Student Management, Competency Improvement, Character Development.